Digital transformation in the agri-food industry: recent applications and the role of the COVID-19 pandemic - Hassoun, Abdo; Marvin, Hans J. P.; Bouzembrak, Yamine; Barba, Francisco J.; Castagnini, Juan Manuel; Pallarés, Noelia; Rabail, Roshina; Aadil, Rana Muhammad; Bangar, Sneh Punia; Bhat, Rajeev; Cropotova, Janna; Maqsood, Sajid; et al. (Frontiers in Sustainable Food Systems, 2023)
Providing food has become more complex because of climate change and other environmental and societal stressors, such as political instability, the growth in the world population, and outbreaks of new diseases, especially the COVID-19 pandemic. In response to these challenges, the agri-food industry has increased its efforts to shift to using more digital tools and other advanced technologies. The transition toward digital has been part of the fourth industrial revolution (called Industry 4.0) innovations that have and are reshaping most industries. This literature review discusses the potential of implementing digital technologies in the agri-food industry, focusing heavily on the role of the COVID-19 pandemic in fostering the adoption of greater digitalization of food supply chains. Examples of the use of these digital innovations for various food applications, and the barriers and challenges will be highlighted. The trend toward digital solutions has gained momentum since the advent of Industry 4.0 and implementations of these solutions have been accelerated by the outbreak of the COVID-19 pandemic. Important digital technology enablers that have high potential for mitigating the negative effects of both the current global health pandemic and the environmental crisis on food systems include artificial intelligence, big data, the Internet of Things, blockchain, smart sensors, robotics, digital twins, and virtual and augmented reality. However, much remains to be done to fully harness the power of Industry 4.0 technologies and achieve widespread implementation of digitalization in the agriculture and food industries.